Self-supporting wood carbon-based electrode material and preparation method and application thereof

By developing self-supporting wood charcoal-based electrode materials, using nitrogen-doped carbon to encapsulate transition metal nanoparticles and porous wood charcoal matrix, the problems of high cost, low stability and high energy consumption of electrode materials in the existing electrolytic hydrogen production technology are solved. , achieving efficient and low-cost electrolytic hydrogen production effect.

CN119433576AInactive Publication Date: 2025-02-14SOUTH CHINA UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411700378.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the high cost, low stability and high energy consumption of electrode materials limit their wide application, and precious metal-based electrode materials have problems of limited reserves and poor long-term stability.

Method used

A self-supported titanium charcoal-based electrode material is developed that combines transition metal nanoparticles with porous titanium charcoal matrix with nitrogen-doped carbon encapsulated to improve catalytic activity and stability through core-shell structures and porous structures.

Benefits of technology

This electrode material exhibits excellent catalytic performance and stability in the process of electrolyzing hydrogen production, reducing energy consumption and improving efficiency. At the same time, its production cost is low and its raw materials are widely sourced, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433576A_ABST
    Figure CN119433576A_ABST
Patent Text Reader

Abstract

The invention discloses a self-supporting wood carbon-based electrode material and a preparation method and application thereof. The self-supporting wood carbon-based electrode material comprises a wood carbon matrix and nitrogen-doped carbon-encapsulated transition metal nanoparticles grown on the surface of the wood carbon matrix in situ, the nitrogen-doped carbon-encapsulated transition metal nanoparticles have a core-shell structure, the core is a transition metal nanoparticle, and the shell is a nitrogen-doped carbon coating layer. The preparation method of the self-supporting wood carbon-based electrode material comprises the following steps: 1) preparing delignified wood; 2) preparing delignified wood loaded with a transition metal source and a nitrogen source; and 3) carbonizing. The self-supporting wood carbon-based electrode material has the advantages of being excellent in catalytic performance, good in structural stability, large in mechanical strength and the like when used as a catalytic electrode material for hydrogen production through water electrolysis, the energy consumption of hydrogen production through water electrolysis can be effectively reduced, the efficiency of hydrogen production through water electrolysis can be improved, the production cost is low, the raw material source is wide, and the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water electrolysis, and in particular to a self-supporting wood carbon-based electrode material and a preparation method and application thereof. Background Art

[0002] Hydrogen has the advantages of light weight, high energy density, high calorific value, and pollution-free combustion, and has a very broad application prospect. However, hydrogen energy is not an energy resource that exists in large quantities in nature, but needs to be obtained through artificial production, a process that is often accompanied by the emission of large amounts of harmful gases such as CO2 and CO. The water electrolysis hydrogen production technology can convert clean intermittent energy such as solar energy, wind energy, and hydropower into controllable and transportable hydrogen energy. It is a simple, environmentally friendly, efficient, and sustainable energy production method, and is currently recognized as the hydrogen production method with the best application prospects.

[0003] The electrolysis of water to produce hydrogen (OWS) reaction is a complex chemical reaction process involving the gas-liquid-solid three-phase interface, which requires the electrode material to have not only high catalytic activity but also good structural stability. Therefore, the design of electrode structure and surface properties is crucial, which will directly affect the utilization efficiency of active substances, gas-liquid transmission rate and electrocatalytic stability. Three-dimensional porous materials such as nickel foam and copper foam have excellent conductivity and rich pore structure, and are suitable for use as carriers for in-situ growth of electrode materials. However, they have problems such as high cost and easy corrosion in the electrolysis environment, and their application is greatly limited. Therefore, researchers are committed to developing low-cost, high-stability three-dimensional porous electrode materials.

[0004] The hydrogen production reaction by water electrolysis includes two key half reactions: the hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode. The kinetics of these two reactions are relatively slow, which leads to a relatively high energy consumption (about 4.5 kWh / Nm 3 H2~5.5kWh / Nm 3 H2). The overpotential of the oxygen production reaction at the anode is usually greater than 1.8V, which is the main source of energy consumption. In order to reduce energy consumption, researchers are committed to developing efficient catalytic electrode materials to reduce the activation energy of the reaction. Precious metal-based electrode materials (such as Pt / C, RuO2 and IrO2) have excellent catalytic performance, but there are problems such as high cost, limited reserves of precious metals, and poor long-term stability, which limit their large-scale application. In order to solve these problems, researchers have developed nitrogen-doped carbon-encapsulated transition metal nanoparticles as an alternative material, but they usually exist in a powder state and need to be integrated into a conductive substrate with a binder when used. This will not only increase the cost of hydrogen production by electrolysis of water, but the binder will also shield some catalytic sites, which will eventually lead to a decrease in the intrinsic catalytic activity of the material.

[0005] Therefore, it is of great significance to develop an electrode material with excellent catalytic performance, good structural stability, low production cost and wide source of raw materials. Summary of the invention

[0006] The purpose of the present invention is to provide a self-supporting wood carbon-based electrode material and a preparation method and application thereof.

[0007] The technical solution adopted by the present invention is:

[0008] A self-supporting wood carbon-based electrode material comprises a wood carbon matrix and nitrogen-doped carbon-encapsulated transition metal nanoparticles in situ grown on the surface of the wood carbon matrix; the nitrogen-doped carbon-encapsulated transition metal nanoparticles have a core-shell structure, wherein the core is the transition metal nanoparticle and the shell is the nitrogen-doped carbon coating layer.

[0009] Preferably, the wood charcoal matrix has a porous structure, the pores are mainly micro / mesopores, and the pore diameter is in the range of 1 nm to 35 nm.

[0010] Preferably, the particle size of the nitrogen-doped carbon-encapsulated metal nanoparticles is in the range of 5 nm to 70 nm.

[0011] Preferably, the transition metal nanoparticles are at least one of nickel nanoparticles, cobalt nanoparticles and iron nanoparticles.

[0012] A method for preparing the self-supporting wood carbon-based electrode material as described above comprises the following steps:

[0013] 1) Slicing the wood transversely and then performing delignification treatment to obtain delignified wood;

[0014] 2) immersing the delignified wood in a transition metal source-nitrogen source mixed solution to obtain the delignified wood loaded with the transition metal source and the nitrogen source;

[0015] 3) The delignified wood loaded with transition metal source and nitrogen source is placed in a protective atmosphere for carbonization to obtain a self-supporting wood carbon-based electrode material.

[0016] Preferably, the wood in step 1) is at least one of shrubs and trees.

[0017] Further preferably, the wood in step 1) is poplar.

[0018] Preferably, the specific operation of the delignification treatment in step 1) includes: immersing the wood chips made by wood slicing in a mixed solution of sodium chlorite-glacial acetic acid at a temperature of 30° C. to 120° C. for a time of 1 h to 10 h.

[0019] Preferably, the transition metal source in step 2) is at least one of a nickel salt, a cobalt salt and an iron salt.

[0020] Preferably, the nitrogen source in step 2) is at least one of amine compounds, amide compounds, organic nitrogen heterocyclic compounds, and nitrogen-containing organic polymers.

[0021] Preferably, the solvent in the transition metal source-nitrogen source mixed solution in step 2) is at least one of ethanolamine, diethanolamine, triethanolamine, N,N-dimethylformamide, ethylenediamine and water.

[0022] Preferably, in step 2), the molar ratio of the transition metal source to the nitrogen source in the transition metal source-nitrogen source mixed solution is 1:0.1 to 5.0.

[0023] Preferably, the immersion in step 2) is carried out at a temperature of 20° C. to 100° C., and the immersion time is 1 h to 48 h.

[0024] Preferably, the protective atmosphere in step 3) is a nitrogen atmosphere or an argon atmosphere.

[0025] Preferably, the carbonization in step 3) is carried out at a temperature of 300° C. to 1200° C., and the carbonization time is 1 h to 20 h.

[0026] An application of the self-supporting wood carbon-based electrode material as described above in hydrogen production by water electrolysis.

[0027] The beneficial effects of the present invention are as follows: the self-supporting wood carbon-based electrode material of the present invention is used as a catalytic electrode material for producing hydrogen by electrolysis of water, has the advantages of excellent catalytic performance, good structural stability, high mechanical strength, etc., can effectively reduce the energy consumption of producing hydrogen by electrolysis of water and improve the efficiency of producing hydrogen by electrolysis of water, and has low production cost, wide source of raw materials, simple preparation method, and is suitable for large-scale industrial production and application.

[0028] Specifically:

[0029] 1) The self-supporting wood charcoal-based electrode material of the present invention contains nitrogen-doped carbon-encapsulated transition metal nanoparticles. The intrinsic electrocatalytic activity can be improved by encapsulating the transition metal nanoparticles in the nitrogen-doped carbon layer and inducing interface lattice distortion, so that the self-supporting wood charcoal-based electrode material can exhibit excellent water electrolysis catalytic performance and stability;

[0030] 2) The nitrogen-doped carbon-encapsulated transition metal nanoparticles in the self-supporting wood carbon-based electrode material of the present invention have a unique core-shell structure, which can expose more active sites, thereby improving the electrocatalytic activity. At the same time, its morphology can be adjusted by controlling the concentration of reactants, reaction temperature, and reaction time. The obtained self-supporting wood carbon-based electrode material has a high specific surface area and high intrinsic electrochemical activity, which is conducive to the contact between the self-supporting wood carbon-based electrode material and the water molecules in the electrolyte, and can promote the electrolysis reaction of the water molecules;

[0031] 3) The self-supporting wood carbon-based electrode material of the present invention has a three-dimensional hierarchical porous structure, low-curvature microchannels, adjustable hydrophilicity / hydrophobicity and good mechanical properties, and can construct an efficient gas-liquid-solid three-phase reaction interface for water electrolysis reaction. Moreover, the use of delignified carbonized wood as a substrate is conducive to further reducing the cost of large-scale production;

[0032] 4) The preparation method of the self-supporting wood carbon-based electrode material of the present invention is simple, efficient, reproducible, and low-cost, and is suitable for large-scale industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Flow chart of the preparation of the self-supporting wood carbon-based electrode material in the examples.

[0034] Figure 2 2 are XRD patterns of Ni-NC@DWC in the embodiment, Ni@DWC in comparative example 1, NC@DWC in comparative example 2, and DWC in comparative example 3.

[0035] Figure 3 The physical image, SEM image, TEM image, SAED image and EDS image of Ni-NC@DWC in the embodiment are shown.

[0036] Figure 4 : Nitrogen adsorption / desorption isotherm curve and pore size distribution diagram of Ni-NC@DWC in the embodiment.

[0037] Figure 5 Schematic diagram of the structure of a three-electrode electrochemical cell for hydrogen evolution reaction and oxygen evolution reaction testing.

[0038] Figure 6 HER performance diagrams and HER overpotential diagrams of Ni-NC@DWC in the embodiment, Ni@DWC in comparative example 1, NC@DWC in comparative example 2, DWC in comparative example 3, and commercial Pt / C electrodes.

[0039] Figure 7The OER performance diagram and OER overpotential diagram of Ni-NC@DWC in the embodiment, Ni@DWC in comparative example 1, NC@DWC in comparative example 2, DWC in comparative example 3 and commercial RuO2 electrode.

[0040] Figure 8 Schematic diagram of the structure of the water electrolysis hydrogen production device for conducting water electrolysis tests.

[0041] Fig. 9 This is a graph showing the voltage test results for producing hydrogen by electrolyzing water using the Ni-NC@DWC in the example and the commercial Pt / C-RuO2 electrode.

[0042] Fig.10 The Ni-NC@DWC in the embodiment is subjected to a current density of 100 mA / cm 2 The stability test results of hydrogen production by water electrolysis under the conditions of . DETAILED DESCRIPTION

[0043] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0044] Example:

[0045] A self-supporting wood carbon-based electrode material, the preparation method of which is as follows (preparation flow chart as shown in Figure 1 shown):

[0046] 1) Slice the poplar wood transversely (perpendicular to the growth direction) to prepare wood chips with a size of 4 cm×2 cm×0.2 cm, wash them with water, dry them in a forced air drying oven at 80° C. overnight, immerse the wood chips in a sodium chlorite-glacial acetic acid mixed solution prepared by 3 g of sodium chlorite, 1 mL of glacial acetic acid and 300 mL of deionized water, heat them in an oil bath at 110° C. for 2 h, take out the wood chips and freeze-dry them at -47° C. for 24 h to obtain delignified wood;

[0047] 2) The delignified wood was immersed in a transition metal source-nitrogen source mixed solution prepared by 1 g of chitosan, 400 μL of glacial acetic acid and 60 mL of a 0.06 m / L NiC4H6O4·4H2O solution, and then placed in a vacuum drying oven at 60°C for 24 h, cooled to room temperature, and then the wood chips were taken out and washed with deionized water several times and freeze-dried at -47°C for 24 h to obtain delignified wood loaded with transition metal sources and nitrogen sources (denoted as Ni-CTS@DW);

[0048] 3) The delignified wood loaded with transition metal source and nitrogen source is placed in a quartz tube furnace, nitrogen is passed through, and the heating rate is controlled to be 3℃ / min from room temperature to 500℃, and the temperature is kept for 1 hour. Then the heating rate is controlled to be 5℃ / min and the temperature is continued to be raised to 1000℃, and the temperature is kept for 3 hours to obtain a self-supporting wood carbon-based electrode material (denoted as Ni-NC@DWC).

[0049] Comparative Example 1:

[0050] A self-supporting wood carbon-based electrode material, the preparation method of which is as follows:

[0051] 1) The delignified wood (same as in the example) was immersed in a transition metal source solution prepared by 3.6 mmol of NiC4H6O4·4H2O and 60 mL of deionized water, and then placed in a vacuum drying oven at 60°C for 24 hours, cooled to room temperature, and then the wood chips were taken out and washed several times with deionized water and freeze-dried at -47°C for 24 hours to obtain delignified wood loaded with a transition metal source;

[0052] 2) The delignified wood loaded with transition metal source is placed in a quartz tube furnace, nitrogen is passed through, and the heating rate is controlled to be 3℃ / min from room temperature to 500℃, and the temperature is kept for 1 hour. Then the heating rate is controlled to be 5℃ / min and the temperature is continued to be raised to 1000℃, and the temperature is kept for 3 hours to obtain a self-supporting wood carbon-based electrode material (denoted as Ni@DWC).

[0053] Comparative Example 2:

[0054] A self-supporting wood carbon-based electrode material, the preparation method of which is as follows:

[0055] 1) The delignified wood (same as in the example) was immersed in a nitrogen source solution prepared by 1 g of chitosan, 400 μL of glacial acetic acid and 60 mL of deionized water, and then placed in a vacuum drying oven at 60° C. for 24 h, cooled to room temperature, and then the wood chips were taken out and washed with deionized water several times and then freeze-dried at -47° C. for 24 h to obtain delignified wood loaded with nitrogen source;

[0056] 2) The delignified wood loaded with nitrogen source is placed in a quartz tube furnace, nitrogen is passed through, and the heating rate is controlled to be 3℃ / min from room temperature to 500℃, and the temperature is kept for 1 hour. Then the heating rate is controlled to be 5℃ / min and the temperature is continued to be raised to 1000℃, and the temperature is kept for 3 hours to obtain a self-supporting wood carbon-based electrode material (denoted as NC@DWC).

[0057] Comparative Example 3:

[0058] A self-supporting wood carbon-based electrode material, the preparation method of which is as follows:

[0059] The delignified wood (same as in the example) was placed in a quartz tube furnace, nitrogen was passed through, and the heating rate was controlled to be 3°C / min from room temperature to 500°C, and kept warm for 1 hour. The heating rate was then controlled to be 5°C / min and continued to be heated to 1000°C, and kept warm for 3 hours to obtain a self-supporting wood carbon-based electrode material (denoted as DWC).

[0060] Performance Testing:

[0061] 1) X-ray diffraction (XRD) patterns of Ni-NC@DWC in the embodiment, Ni@DWC in Comparative Example 1, NC@DWC in Comparative Example 2, and DWC in Comparative Example 3 are shown in FIG. Figure 2 shown.

[0062] Depend on Figure 2 It can be seen that: the diffraction peak at 26.3° is attributed to the low-curvature porous delignified wood charcoal (DWC) framework; with the introduction of Ni, diffraction peaks at 44.5°, 51.8° and 76.4° belonging to the (111), (200) and (220) crystal planes of metallic nickel were observed in Ni-NC@DWC and Ni@DWC, respectively; due to nitrogen-doped carbon encapsulation, the diffraction peak corresponding to metallic nickel in Ni-NC@DWC is weak; in summary, it can be seen that a self-supporting wood charcoal-based electrode material with the expected composition and structure was indeed prepared in the embodiment.

[0063] 2) The physical image, scanning electron microscope (SEM) image, transmission electron microscope (TEM) image, selected area electron diffraction (SAED) image and energy dispersive X-ray spectroscopy (EDS) image of Ni-NC@DWC in the embodiment are as follows: Figure 3 (a is a real picture, b and c are SEM pictures at different magnifications, d to g are TEM pictures at different magnifications, the small picture in the upper right corner of c is a structural schematic diagram, the small picture in the upper right corner of d is a particle size distribution diagram, h is a SAED picture, and i is an EDS picture).

[0064] Depend on Figure 3 From a in the figure, we can see that Ni-NC@DWC is in the form of flakes with a size of 1cm×1cm×0.05cm, and can be directly used as a self-supporting integrated electrode;

[0065] Depend on Figure 3 From b, we can see that Ni-NC@DWC retains the low-curvature channel structure of natural wood;

[0066] Depend on Figure 3 From the figure c, we can see that the nitrogen-doped carbon-encapsulated nickel nanoparticles (Ni-NC) in Ni-NC@DWC are uniformly dispersed in the low-curvature microchannels of DWC;

[0067] Depend on Figure 3From d in the figure, we can see that the nitrogen-doped carbon-encapsulated nickel nanoparticles (Ni-NC) in Ni-NC@DWC are uniformly dispersed, with an average particle size of about 30 nm (the particle size distribution is in the range of 5 nm to 70 nm);

[0068] Depend on Figure 3 From the figure e, we can see that the Ni nanoparticles in Ni-NC@DWC are encapsulated by the nitrogen-doped carbon layer, and the lattice spacings of the metallic nickel (111) crystal plane and the graphite carbon (002) crystal plane are 0.22nm and 0.34nm, respectively.

[0069] Depend on Figure 3 From f and g in Fig. 1, it can be seen that the Ni nanoparticles in Ni-NC@DWC have abundant lattice distortion;

[0070] Depend on Figure 3 From h in the figure, we can see that the two different groups of diffraction rings in Ni-NC@DWC belong to metallic nickel and graphite carbon respectively;

[0071] Depend on Figure 3 From the i in the figure, we can see that there are C, N and Ni elements in Ni-NC@DWC, and each element is evenly distributed;

[0072] In summary, it can be seen that the self-supporting wood carbon-based electrode material with the expected composition and structure was indeed prepared in the examples.

[0073] 3) The nitrogen adsorption / desorption isotherm and pore size distribution of Ni-NC@DWC in the embodiment are shown in Figure 4 (a is the nitrogen adsorption / desorption isotherm curve, b is the pore size distribution diagram).

[0074] Depend on Figure 4 From a in the figure, we can see that Ni-NC@DWC exhibits a typical type IV nitrogen adsorption / desorption isotherm with an obvious H2-type hysteresis loop, indicating that Ni-NC@DWC has a rich micro / mesoporous structure. The specific surface area of ​​Ni-NC@DWC is calculated to be 180.0 m 2 / g, the average pore diameter is 4.35nm, and the average pore volume is 0.2134cm 3 / g, indicating that Ni-NC@DWC has a high specific surface area, which is beneficial to expose abundant active sites to improve the electrocatalytic performance;

[0075] Depend on Figure 4 From b, we can see that the pore structure of Ni-NC@DWC is mainly micro / mesopores, and the pore size distribution is in the range of 1nm to 35nm, indicating that Ni-NC@DWC has a rich pore structure, which is beneficial to increase the contact area between the reactants and the catalyst, and provides favorable conditions for constructing an efficient gas-liquid-solid three-phase reaction interface.

[0076] 4) Hydrogen evolution reaction and oxygen evolution reaction test: The self-supporting wood carbon-based electrode material sample was fixed on a platinum electrode as a working electrode (working area of ​​10 mm × 10 mm), a Hg / HgO electrode as a reference electrode, a graphite rod with a diameter of about 6 mm as a counter electrode, and a KOH solution with a concentration of 1 mol / L (pH value of about 13.8) as an electrolyte to assemble a three-electrode electrochemical cell (schematic diagram as shown in the figure). Figure 5 As shown in the figure, a is an electrochemical workstation, b is a single-chamber electrolytic cell, c is a working electrode, d is a counter electrode, and e is a reference electrode), and then a linear sweep voltammetry (LSV) test was performed using a Chenhua CHI660E electrochemical workstation (the scan rate was 5 mV / s, and all data were 95% current impedance (IR) compensated to ensure accuracy).

[0077] a) HER performance diagram and HER overpotential diagram of Ni-NC@DWC in Example, Ni@DWC in Comparative Example 1, NC@DWC in Comparative Example 2, DWC in Comparative Example 3 and commercial Pt / C electrode (denoted as Pt / C) as shown in Figure 6 (a is the HER performance diagram, b is the HER overpotential diagram).

[0078] Depend on Figure 6 From a in the figure, we can see that Ni-NC@DWC has the best HER activity;

[0079] Depend on Figure 6 From b, we can see that Ni-NC@DWC only needs an ultra-low overpotential of 17mV and 24mV to obtain 50mA / cm 2 and 100mA / cm 2 The current density is much better than Ni@DWC (η 50 =131mV,η 100 =169mV), NC@DWC(η 50 =454mV,η 100 =479mV) and commercial Pt / C electrode (η 50 =242mV,η 100 =286mV).

[0080] b) OER performance diagram and OER overpotential diagram of Ni-NC@DWC in Example, Ni@DWC in Comparative Example 1, NC@DWC in Comparative Example 2, DWC in Comparative Example 3 and commercial RuO2 electrode (denoted as RuO2) as shown in Figure 7 (a is the OER performance diagram, b is the OER overpotential diagram) as shown.

[0081] Depend on Figure 7 From a in the figure, we can see that Ni-NC@DWC has the best OER activity;

[0082] Depend on Figure 7 From the figure b, we can see that Ni-NC@DWC only needs ultra-low overpotentials of 211 mV and 377 mV to obtain 10 mA / cm 2 and 100mA / cm 2 The current density is much better than Ni@DWC (η 10 =266mV,η 100 =421mV), Ni@DWC(η 10 =348mV,η 100 =604mV) and commercial RuO2 electrode (η 10 =309mV,η 100 =523mV).

[0083] 5) Electrochemical performance test and stability test of water electrolysis reaction: Two pieces of self-supporting wood carbon-based electrode materials of the same size were placed as cathode and anode respectively in an H-type double-chamber electrolyzer to assemble a water electrolysis hydrogen production device (schematic diagram as shown in Figure 8 As shown, a in the figure is a single-chamber electrolytic cell, b is the cathode, and c is the anode), and then an electrolysis water test is carried out (the commercial Pt / C-RuO2 electrode is used as a control, denoted as Pt / C-RuO2).

[0084] a) The voltage test results of the Ni-NC@DWC in the embodiment and the commercial Pt / C-RuO2 electrode for water electrolysis and hydrogen production are shown in Figure 2. Fig. 9 shown.

[0085] Depend on Fig. 9 From a in the figure, we can see that the performance of Ni-NC@DWC in water electrolysis and hydrogen production is better than that of commercial Pt / C-RuO2 electrode;

[0086] Depend on Fig. 9 From b, we can see that Ni-NC@DWC only needs 1.44V to achieve 10mA / cm 2 The current density of 100 mA / cm2 is 1.61 V, while the commercial Pt / C-RuO2 electrode requires a voltage of 1.56 V to achieve the same current density. 2 The current density of Ni-NC@DWC is 2.0 V, while the commercial Pt / C-RuO2 electrode requires a voltage of 1.96 V to achieve the same current density, indicating that the performance of Ni-NC@DWC is significantly better than that of the commercial Pt / C-RuO2 electrode.

[0087] b) Ni-NC@DWC in the embodiment at a current density of 100 mA / cm 2 The stability test results of water electrolysis and hydrogen production under the conditions of Fig.10 shown.

[0088] Depend on Fig.10 It can be seen that the Ni-NC@DWC assembled water electrolysis hydrogen production device has a current density of 100mA / cm 2 There was no obvious potential decay after continuous operation for 130 h under the conditions, showing excellent stability.

[0089] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A self-supporting wood carbon-based electrode material, characterized in that: The composition includes a wood charcoal matrix and nitrogen-doped carbon-encapsulated transition metal nanoparticles in situ grown on the surface of the wood charcoal matrix; the nitrogen-doped carbon-encapsulated transition metal nanoparticles have a core-shell structure, the core is the transition metal nanoparticles, and the shell is the nitrogen-doped carbon coating layer.

2. The self-supporting wood carbon-based electrode material according to claim 1, characterized in that: The wood carbon matrix has a porous structure, the pores are mainly micro / mesopores, and the pore diameters are in the range of 1nm to 35nm.

3. The self-supporting wood carbon-based electrode material according to claim 1 or 2, characterized in that: The particle size of the nitrogen-doped carbon-encapsulated metal nanoparticles is in the range of 5nm to 70nm.

4. The self-supporting wood carbon-based electrode material according to claim 1 or 2, characterized in that: The transition metal nanoparticles are at least one of nickel nanoparticles, cobalt nanoparticles and iron nanoparticles.

5. A method for preparing a self-supporting wood carbon-based electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) Slicing the wood transversely and then performing delignification treatment to obtain delignified wood; 2) immersing the delignified wood in a transition metal source-nitrogen source mixed solution to obtain the delignified wood loaded with the transition metal source and the nitrogen source; 3) The delignified wood loaded with transition metal source and nitrogen source is placed in a protective atmosphere for carbonization to obtain a self-supporting wood carbon-based electrode material.

6. The preparation method according to claim 5, characterized in that: In step 1), the wood is at least one of shrubs and trees; in step 2), the transition metal source is at least one of nickel salts, cobalt salts, and iron salts; in step 2), the nitrogen source is at least one of amine compounds, amide compounds, organic nitrogen heterocyclic compounds, and nitrogen-containing organic polymers.

7. The preparation method according to claim 5 or 6, characterized in that: Step 2) The molar ratio of the transition metal source to the nitrogen source in the transition metal source-nitrogen source mixed solution is 1:0.1-5.

0.

8. The preparation method according to claim 5 or 6, characterized in that: Step 2) The immersion is carried out at a temperature of 20°C to 100°C and the immersion time is 1h to 48h.

9. The preparation method according to claim 5 or 6, characterized in that: Step 3) The carbonization is carried out at a temperature of 300° C. to 1200° C., and the carbonization time is 1 h to 20 h.

10. Use of the self-supporting wood carbon-based electrode material according to any one of claims 1 to 4 in producing hydrogen by electrolysis of water.

Citation Information

Patent Citations

  • Electromagnetic wave shielding breathable porous carbon composite material and preparation method and application thereof

    CN113271758A

  • Bamboo-like carbon nanotube composite material based on wood carbonized porous structure and preparation method of bamboo-like carbon nanotube composite material

    CN114314563A

  • Nitrogen-doped supported nano-catalyst as well as preparation method and application thereof

    CN116791128A